Aerial Photography for Mapping in UNIMAS Campus (poster) - Universiti Malaysia Sarawak, Institute Of Social Informatics and Technological Innovations (Universiti Malaysia Sarawak, (UNIMAS), 2013)
A poster exhibited at UNIMAS R&D Expo